Islamic Integration And Health - Purnamaniswaty Yunus (Journal of Research and Multidisciplinary, 2019)
This article aims to elaborate on Islam and health issues with a focus on the relationship between Islam and health. The data refer to authoritative sources of Islam, especially the hadith books on health that were explored thematically supported by several other sources such as al-Tibb al-Nabawi and some relevant literature. As a result, Islam adheres to the principle of preventive medicine (al-wiqayat) compared to the principle of healing medicine (al-'ilaj). This is in line with the principle of "preventing mafsadat prioritized compared to taking benefit". Detection of the type of disease and its causes must be carried out earlier before taking the treatment step. For this reason, physical illness is dealt with according to the procedure as a type of non-physical illness carried out a spiritual approach.